Permissive underfeeding versus target enteral feeding in adult critically ill patients (PermiT Trial): a study protocol of a multicenter randomized controlled trial - Arabi, Yaseen M; Haddad, Samir H; Aldawood, Abdulaziz S; Al-Dorzi, Hasan M; Tamim, Hani M; Sakkijha, Maram; Jones, Gwynne; McIntyre, Lauralyn; Mehta, Sangeeta; Solaiman, Othman; Sadat, Musharaf; Afesh, Lara; et al. (Université d'Ottawa | University of Ottawa, 2012)
Abstract Background Nutritional support is an essential part of the management of critically ill patients. However, optimal caloric intake has not been systematically evaluated. We aim to compare two strategies of enteral feeding: permissive underfeeding versus target feeding. Method/Design This is an international multi-center randomized controlled trial in critically ill medical- surgical adult patients. Using a centralized allocation, 862 patients will be randomized to permissive underfeeding or target feeding. Patients in the permissive group receive 50% (acceptable range is 40% to 60%) of the calculated caloric requirement, while those in the targeted group receive 100% (acceptable range 70% to 100%) of the calculated caloric requirement. The primary outcome is 90-day all-cause mortality. Secondary outcomes include ICU and hospital mortality, 28-day, and 180-day mortality as well as health care-associated infections, organ failure, and length of stay in the ICU and hospital. The trial has 80% power to detect an 8% absolute reduction in 90-day mortality assuming a baseline risk of death of 25% at an alpha level of 0.05. Discussion Patient recruitment started in November 2009 and is currently active in five centers. The Data Monitoring Committee advised continuation of the trial after the first interim analysis. The study is expected to finish by November 2013. Trial registration Current Controlled Trials ISRCTN68144998